2010
DOI: 10.1007/s12103-010-9090-2
|View full text |Cite
|
Sign up to set email alerts
|

Officer Attitudes and Management Influences on Police Work Productivity

Abstract: Police officers are afforded a high degree of discretion in the exercise of their authority, and the control of this discretion is an important issue. While it is assumed that individual officer attitudes and preferences shape their discretionary activity, these officers are also members of a paramilitary organization with leaders appointed over them. The present study explored the influence of both officer attitudes and supervisor influences to explain variation in officer traffic citation issuing rates. Hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
1
46
0
1
Order By: Relevance
“…While some studies found officer attitudes to be significant predictors of officer work behaviors (Brehm & Gates, 1993Johnson, 2011), others found no significant relationship between officer attitudes and work behaviors (Engel & Worden, 2003;Paoline et al, 2000;Worden, 1989). Perhaps, as the social psychological literature would suggest, these inconsistent findings were the result of differences in work environments across these studies.…”
Section: Literature Reviewmentioning
confidence: 83%
See 4 more Smart Citations
“…While some studies found officer attitudes to be significant predictors of officer work behaviors (Brehm & Gates, 1993Johnson, 2011), others found no significant relationship between officer attitudes and work behaviors (Engel & Worden, 2003;Paoline et al, 2000;Worden, 1989). Perhaps, as the social psychological literature would suggest, these inconsistent findings were the result of differences in work environments across these studies.…”
Section: Literature Reviewmentioning
confidence: 83%
“…The remaining agency-level variables, such as the volume of calls for service and the average span of control within the organization, had little bearing on the proportion of domestic violence calls that resulted in an arrest, explaining only 1.6% of the variance. 2 Finally, since both Engel and Worden (2003) and Johnson (2011) found that the actual enforcement attitudes of the supervisors were unassociated with the attitudes the officers' perceived they held, we decided to examine the same. For this analysis, we used only the officer-level data and, for each case, added as a variable the officer's supervisor's response to the statement, "I believe that domestic violence enforcement is a personal priority for me."…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations